The single supervisory mechanism or “SSM”, part one of the Banking Union - Eddy Wymeersch (National Bank of Belgium, 2014)
The Regulation on the Single Supervisory Mechanism mandates the European Central Bank to exercise prudential supervision on the banks located in the Euro area, whether directly by the Bank's own services for the significant banks, or indirectly by the national prudential supervisors but under the general guidance of the ECB for the less significant banks. The paper gives a detailed analysis of the new regime, its scope, the consequences for the existing supervisory systems, especially the home-host attribution of competences and the cooperation between the ECB and the national supervisors, the consequences for the non-euro Member States and for the third country jurisdictions. This regime is likely to substantially modify the existing supervisory landscape. It is the first step towards the Banking Union and is to be followed by legislative instruments on Bank Recovery and Resolution Directive, the Regulations on a Single Resolution Mechanism and on Deposit Guarantee Schemes. These three measures should allow dealing with defaulting banks without calling on the taxpayers.
Keywords: G20; G28; G38; 330; Regulation Single Supervisory Mechanism; European Central Bank; European Banking Authority; banking prudential supervision; home-host; banking crisis; Bankenregulierung; Bankenaufsicht; Zentralbank; Eurozone; EU-Staaten